The Flavor of Thinking (mdwPress, 2026)
The relation between art and philosophy is highly precarious. To explore this complex connection, the contributors to this volume have structured their texts around key questions such as: What image of thought emerges when artistic practices are integrated into philosophical research? How does the conceptual personae of philosophers change when they become artist-philosophers? And how do writing and working methods shift when crossing the boundaries between art and philosophy? This approach opens up a holistic perspective on strategies, methodologies, and concrete examples of writing and reading by philosopher-artists and artistic researchers who strive toward a genuine crossover between art and philosophy.